Assessment of reperfusion of the infarct zone after acute myocardial infarction by serial cardiac troponin T measurements in serum. Issue 3 (March 1994) - Remppis, A.; Scheffold, T.; Karrer, O.; Zehelein, J.; Hamm, C.; Grünig, E.; Bode, C.; Kübler, W.; Katus, H. A.
Abstract : BACKGROUND--The purpose of this study was to derive indices of reperfusion and non-reperfusion after acute myocardial infarction (AMI) from changes in serum concentrations of cardiac troponin T and to test the predictive value of these indices. METHODS--The indices were derived from a retrospective analysis of changes in serum troponin T concentration in 71 patients given thrombolytic treatment who had immediate and late angiography (group 1). These troponin T indices were first tested in a blinded and prospective study of 53 consecutive patients eligible for thrombolytic therapy (group 2). They were then used for the non-invasive assessment of reperfusion of AMI in 48 patients (group 3). RESULTS--In group 1 troponin T serum concentration curves were biphasic in patients who had reperfusion < or = 5.8 h after the onset of symptoms. Release of the cytosolic troponin T pool resulted in a peak at 14 h and ended at 38 h. The probability of reperfusion was > 95% when the ratio of peak cytosolic troponin T concentration to concentration at 38 h (PV1/38) exceeded 1.42 or the ratio of troponin T concentration at 14 h to that at 38 hours (14/38) exceeded 1.09. The probability of the presence of non-reperfused AMI was < 5% when troponin T PV1/38 and 14/38 ratios were < 0.99 and < 0.84 respectively. These discriminatory values of troponin T indices correctly classified (efficiency 96%) 48 of the 53 group 2 patients in whom immediate and late angiography were performed. When troponin T indices were used to classify 48 group 3 patients who were not studied by immediate angiography, thrombolytic therapy was deemed to have been successful in 82% of the treated patients, with spontaneous recanalisation in 11% and 23% of the non-treated patients assessed by PV1/38 and 14/38 respectively. CONCLUSION--The PV1/38 or 14/38 ratios of serum troponin T concentration indicated the effectiveness of thrombolytic therapy in achieving reperfusion of AMI.